Utilization of Blockchain Technology to Improve Security and Transparency of Information Systems - Tb. M. Adrie Admira; Panji Rahman (Information Technology Studies Journal (ITECH), 2024)
The integration of Blockchain technology with artificial intelligence (AI) and the Internet of Things (IoT) has become a major focus in efforts to increase the security and transparency of information systems. This research aims to investigate findings related to the use of Blockchain technology to increase the security and transparency of information systems through integration with artificial intelligence and the Internet of Things. The research method used is a systematic literature review that investigates various related research articles in scientific databases. The discussion results show that this integration offers innovative solutions to improve data security, access control, and privacy protection in various application domains. The implications of this research highlight the importance of considering the challenges and practical implications of adopting this integration, as well as identifying trends and future research directions in this domain.